2017
DOI: 10.1039/c7cc03669h
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical synthesis of phthalides via anodic activation of aromatic carboxylic acids

Abstract: A new electrochemical methodology allows to easily generate aroyloxy radicals from their corresponding aromatic carboxylic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…In 2017, Lam and co‐workers reported the electrochemical synthesis of phthalides by using anodically generated aroyloxy radicals in combination with aliphatic carboxylic acid as alkylating agent precursors (Scheme ) . They proposed that aroyloxy and alkyl radicals are key intermediates of this reaction.…”
Section: Ester C−o Bond Formation Through Electrolysis Of Carboxylic mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, Lam and co‐workers reported the electrochemical synthesis of phthalides by using anodically generated aroyloxy radicals in combination with aliphatic carboxylic acid as alkylating agent precursors (Scheme ) . They proposed that aroyloxy and alkyl radicals are key intermediates of this reaction.…”
Section: Ester C−o Bond Formation Through Electrolysis Of Carboxylic mentioning
confidence: 99%
“…The reactioni su seful for the synthesis In 2017, Lam and co-workers reported the electrochemical synthesis of phthalides by using anodically generated aroyloxy radicals in combination with aliphatic carboxylic acid as alkylating agent precursors (Scheme 17). [25] They proposed that aroyloxy and alkyl radicals are key intermediates of this reaction. The electrogenerated alkyl radicalf rom the aliphatic carboxylic acid might oxidize the aromatic carboxylate to form the aroyloxy radical.…”
Section: Lactone Formation Through Intramolecular Trapping Of Intermementioning
confidence: 99%
“…[9] With this in mind, we have previously employed aroyloxy radicals,f ormed via anodic oxidation of aromatic carboxylic acids,t osynthesise al ibrary of functionalised phthalides under mild and green conditions. [38] While the photochemical synthesis of g-butyrolactones has recently been reported, this methodology relies on highly toxic and expensive solvent mixtures and metal catalysts. Moreover,itiscurrently limited to sp 2 -sp 3 coupling cascades and requires the use of ac aesium salt.…”
mentioning
confidence: 99%
“…Furthermore,t hey provide ac heap and readily available source of alkyl radicals which undergo an unusual metal-free sp 3 -sp 3 cross-coupling at the surface of the electrode (Table 1). [38] After optimisation, [40] it was found that the substituted lactone 2 was formed in higher yields (30 %) when 1 was added to amethanolic solution of co-acid and potassium hydroxide,with no lactone formation observed in DMF or acetonitrile.Alcohols,water, as well as mixtures of both are known to favour the mono-electronic anodic oxidation of carboxylic acids while other solvents tend to favour abi-electronic oxidation. [13] Platinum has shown to be the most appropriate electrode material for the reaction.…”
mentioning
confidence: 99%
“…Synthetic organic electrochemistry takes its roots from Faraday's 16 and Kolbe's 17 classic works on electrolysis of aliphatic carboxylic acids. Although numerous transformations have been developed ever since [18][19][20][21][22][23] and many of them have been successfully used in several industrial processes, 22,24 the potential of preparative organic electrochemistry remains underestimated even though electrosynthesis represents one of the safest and greenest methods to perform organic redox reactions. Hopefully, the new commercially available Electrasyn 2.0 electrolysis setup will facilitate the use of electrosynthesis in organic synthetic laboratories.…”
mentioning
confidence: 99%